2022
DOI: 10.3389/fnagi.2022.872867
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Brain-Age in Psychotic Psychopathology: Evidence for Transdiagnostic Neurodevelopmental Origins

Abstract: Schizophrenia is characterized by abnormal brain structure such as global reductions in gray matter volume. Machine learning models trained to estimate the age of brains from structural neuroimaging data consistently show advanced brain-age to be associated with schizophrenia. Yet, it is unclear whether advanced brain-age is specific to schizophrenia compared to other psychotic disorders, and whether evidence that brain structure is “older” than chronological age actually reflects neurodevelopmental rather tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 88 publications
(90 reference statements)
3
4
1
Order By: Relevance
“…Consistent with previous studies ( Cole, 2020 ; Demro et al, 2022 ), structural MRI features showed prominent potential for the prediction of brain age. In the present study, brain age-related GMV features were mainly distributed in the subcortical system (e.g., thalamus and hippocampus) and dorsal attention network.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies ( Cole, 2020 ; Demro et al, 2022 ), structural MRI features showed prominent potential for the prediction of brain age. In the present study, brain age-related GMV features were mainly distributed in the subcortical system (e.g., thalamus and hippocampus) and dorsal attention network.…”
Section: Discussionsupporting
confidence: 90%
“…Chen et al also found that the normalized predicted age difference did not show a significant correlation with the duration of illness in schizophrenia 23 . We found that previous studies had inconsistent results on the association between the brain age gap and duration of illness in individuals with schizophrenia 14,17,21,22 . The relevant studies are still limited.…”
Section: Introductioncontrasting
confidence: 59%
“…Huang and colleagues indicated that the brain age gap of young individuals with schizophrenia was larger than that of healthy controls; however, the same result was not observed in middle-aged individuals with schizophrenia 21 . Demro et al demonstrated that the disease course of psychotic illness was not significantly correlated with their brain age gap 14 . Chen et al also found that the normalized predicted age difference did not show a significant correlation with the duration of illness in schizophrenia 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Premature, advanced, or accelerated brain aging are terms used to describe the gap between chronological age and estimated brain age derived from different machine learning algorithms. Accelerated brain aging is a non-specific observation that has been reported in many conditions such as major depression ( 47 50 ), psychosis ( 51 , 52 ), obsessive compulsive disorder ( 53 ), traumatic brain injury ( 54 , 55 ), tobacco smoking ( 56 ), diabetes mellitus ( 57 , 58 ), glioma patients following radiotherapy ( 59 ), and in healthy individuals with inadequate sleep ( 60 ). Few studies have reported negative association between accelerated brain aging and cognitive performance in patients with major psychoses ( 51 ), in older patients with depressive symptoms ( 61 ) and in patients with traumatic brain injury ( 54 ).…”
Section: Introductionmentioning
confidence: 99%